The Mediation Role of Organizational Commitment on the Influence of Participatory Leadership, Competence on Lecturer Performance - Irnawati, Wati; Nuryani, Lilis Kholisoh (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study examines the mediating role of organizational commitment on the influence of participatory leadership and competence on lecturer performance. This research consists of two independent variables, participative leadership and competence, and one mediating variable, organizational commitment, and one dependent variable, lecturer performance. This study uses a quantitative explanative approach with a survey approach. The test was carried out at the Guna Nusantara College of Social and Political Sciences (STISIP). This study uses the Partial Least Square (PLS) analysis method using Smart PLS. The results of the study show that participatory leadership has a significant effect on lecturer performance. The higher the participative leadership, the higher the performance of the lecturers. Competence has a significant effect on lecturer performance. The higher the competency, the higher the lecturer's performance. Competence has a significant effect on organizational commitment. The higher the competence, the higher the organizational commitment. Organizational commitment has a significant effect on lecturer performance. The higher the organizational commitment, the higher the performance of lecturers. There is no indirect effect of participatory leadership on performance through organizational commitment. There is an indirect effect of competency on performance through organizational commitment.